Satisfaction with radiotherapy care among cancer patients treated in Germany: secondary analysis of a large multicenter study - Fabian, Alexander; Rühle, Alexander; Domschikowski, Justus; Trommer, Maike; Wegen, Simone; Becker, Jan-Niklas; Wurschi, Georg; Böke, Simon; Sonnhoff, Mathias Alexander; Fink, Christoph Andreas; Käsmann, Lukas Tobias; Schneider, Melanie; et al. (Strahlentherapie und Onkologie, 2023)
Patient satisfaction with healthcare has been linked to clinical outcomes and regulatory agencies demand its regular assessment. Therefore, we aimed to investigate patient satisfaction with radiotherapy care and its determinants.
Gesehen am 23.04.2024